Modified Design of Pin-on-Ring Tribometer for Hip Joint Prostheses Measurement; Case Study on Salat Activity - Khafidh, Muhammad; Jamari, Jamari; Sulardjaka, Sulardjaka; Tauviqirrahman, Mohamad; Heide, Emile van der (UI Scholars Hub, 2014)
Total hip replacement (THR) is one of the most successful orthopedic surgical procedures for replacing a broken hip joint. In THR, wear may occur at the articulating surface of the acetabular cup and the femoral head. In Indonesia, the country with the largest Muslim population in the world, most of the inhabitants do salat (praying) every day. THR users are banned from doing salat for fear it will damage the hip joint prostheses. The previous wear calculation methods on the hip joint prostheses use the gravimetric, coordinate measuring machine (CMM), profiler, and geometric method. The disadvantages of the previous methods are that the geometry of the wear patch and the wear volume are only known at the end of the experiment, so they cannot be used to calculate the specific wear rate values in real time. So far, in every modeling of the hip joint prostheses, the values of the specific wear rate are assumed to be constant. This paper reports on the design modification of a pin-on-ring tribometer that is used to measure the wear volumes in hip joint prostheses. The result shows that modifications of the femoral head holder, reciprocating motion, elastic joint, and extra displacement transducer is needed to get the specific wear rate value. The calculation method to find the delta volume that is the value of displacement less than the displacement minimum (δmin) is based on a graph, while the calculation method to find the delta volume that is the value of displacement that is more than the displacement minimum (δmin) is based on an equation. In the salat test protocol, the longest test time was during the sujud (prostration) motion, which took 1034.17 minutes in the experiment.